Pregnant women’s attitudes toward smoking posing danger to foetuses and newborns - Bucholc, Marzena; Wiktor, Henryk; Buchajczuk, Celina (Polish Journal of Public Health, 2012)
Introduction. Smoking cigarettes is the most common addiction, also observed in women before and during pregnancy.Aim. This study presents the attitudes of pregnant women towards smoking and the related risks to the foetus and the newborn.Material and methods. The study was based on the author’s questionnaire and analysis of medical records.It was conducted in obstetric-neonatal units of three hospitals in Lublin, from July to September 2010.Results. In the observed group, 64.5% women never smo-ked cigarettes. The remaining 35.5% admitted to the habit. Of the latter group 57.1% continued smoking during pregnancy, and 30 (42.9%) stopped. Cigarette smoking during pregnancy was statistically dependent (p